2021
DOI: 10.5603/njo.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer in the older population

Abstract: Fifty percent of new diagnoses of colorectal cancer are made in patients aged over 70 years, and 25% are aged 80 years or over. Older patients tend to have locally advanced colon cancer, with negative lymph nodes and without distant metastasis. Frequently the colon cancer is located on the right side. There is still a belief that older patients can not manage curative treatment regimens. This is based on the results of older studies showing higher rates of short-term morbidity and mortality. At present, we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This case shows that regardless of the medical specialty, attention should be paid to changes in other organs, including those that are not directly examined. Most colorectal cancers are diagnosed in older patients, over 70 years of age [1]. This patient was in her 50s at diagnosis, so it can be concluded that one should be vigilant for cancer, even if the patient is not directly in the high-risk age group.…”
mentioning
confidence: 94%
“…This case shows that regardless of the medical specialty, attention should be paid to changes in other organs, including those that are not directly examined. Most colorectal cancers are diagnosed in older patients, over 70 years of age [1]. This patient was in her 50s at diagnosis, so it can be concluded that one should be vigilant for cancer, even if the patient is not directly in the high-risk age group.…”
mentioning
confidence: 94%